The Impact of NCT Dreams ad Brand Ambassadors and Brand Image on Consumer Impulsive Buying Behavior: A Case Study of Lemonilo Instant Noodle Consumers - Nufih Wahda Maulidya; Hanik Fitriani (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
Indonesia is the country with the second highest level of instant noodle consumption after China. Lemonilo instant noodle products are in the expensive category, as evidenced by sales data for Lemonilo instant noodles in January 2022 which only reached 6.3%. Meanwhile, after collaborating with NCT Dream as brand ambassador, sales figures for Lemonilo instant noodles rose to 154.9%. To increase sales and expand its market, Lemonilo attracts consumer interest by collaborating with NCT Dream as a brand ambassador and adding a member photocard bonus in the packaging as well as an online fansign lottery so that it motivates its fans to do impulsive buying. This research aims to determine the influence of brand ambassadors on impulsive buying, brand image on impulsive buying, and brand ambassadors and brand image on impulsive buying. This type of research is quantitative with data collection methods using questionnaires. Researchers took samples from a population of 96 NCT Dream fans who bought Lemonilo instant noodle products. The research results show that: 1) The brand ambassador variable has a positive and significant effect on impulsive buying, 2) The brand image variable has a positive and significant effect on impulsive buying, 3) The brand ambassador and brand image variables simultaneously have a significant effect on impulsive buying. The coefficient of determination of brand ambassador and brand image has an influence of 41.7% on impulsive buying and 58.3% is influenced by other factors. Keywords: Brand Ambassador, Brand Image, Impulsive Buying